2018
DOI: 10.1016/j.icheatmasstransfer.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Passive scalar diffusion in three-dimensional turbulent rectangular free jets with numerical evaluation of turbulent Prandtl/Schmidt number

Abstract: The passive scalar spreading of fluids with laminar Prandtl or Schmidt number, , Pr Sc , equal to 1 in turbulent rectangular submerged free jets is analyzed by means of numerical simulation and theoretical analysis in the Reynolds number range 5000-40,000. The numerical investigation is carried out by means of a three-dimensional (3D) Large Eddy Simulation (LES) approach with the dynamic Smagorinsky model. A new mathematical model allows to obtain a simplified description of the passive scalar spreading in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
2
14
1
Order By: Relevance
“…Standard models with constant coe cient are usually too dissipative in the initial free shear layer of the jet, thus delaying its transition. Dynamic models can overcome this issue [50][51][52][53], potentially at the price of stability, which is not always desirable when simulating complex flows. This is one reason why implicit LES (or ILES) has been widely adopted in the literature [21,54,55], since the absence of excessive SGS viscosity allows accurate capture of the jet behaviour, especially near the nozzle.…”
Section: Methodsmentioning
confidence: 99%
“…Standard models with constant coe cient are usually too dissipative in the initial free shear layer of the jet, thus delaying its transition. Dynamic models can overcome this issue [50][51][52][53], potentially at the price of stability, which is not always desirable when simulating complex flows. This is one reason why implicit LES (or ILES) has been widely adopted in the literature [21,54,55], since the absence of excessive SGS viscosity allows accurate capture of the jet behaviour, especially near the nozzle.…”
Section: Methodsmentioning
confidence: 99%
“…Self-similar laws for the momentum spreading in turbulent jets have been proposed in the past, as Tollmien (1926), Kuethe (1935), Zel'dovich (1937, Görtler (1942), Batchelor (1954, Angelino et al (2016), Boghi et al (2016), also if several papers have concluded of its impossible formulation, and can be exemplified by Tennekes and Lumley (1963). Self-similar solutions for the passive scalar diffusion in turbulent jets have been proposed, as well, in Boghi et al (2017) and Di Venuta et al (2018a).…”
Section: Introductionmentioning
confidence: 98%
“…Self-similarity in passive scalar spreading was studied with DNS in [17]. The mean passive scalar was found self-similar in the FDR, with the Large Eddy Simulation (LES) approach, for round [18] and planar jets [19].…”
Section: Introductionmentioning
confidence: 99%